Oncolytic Effects of a Novel Influenza A Virus Expressing Interleukin-15 from the NS Reading Frame - van Rikxoort, Marijke; Michaelis, Martin; Wolschek, Markus; Muster, Thomas; Egorov, Andrej; Seipelt, Joachim; Doerr, Hans Wilhelm; Cinatl, Jindrich, Jr (PLOS ONE, 2012)
Oncolytic influenza A viruses with deleted NS1 gene (delNS1) replicate selectively in tumour cells with defective interferon response and/or activated Ras/Raf/MEK/ERK signalling pathway. To develop a delNS1 virus with specific immunostimulatory properties, we used an optimised technology to insert the interleukin-15 (IL-15) coding sequence into the viral NS gene segment (delNS1-IL-15). DelNS1 and delNS1-IL-15 exerted similar oncolytic effects. Both viruses replicated and caused caspase-dependent apoptosis in interferon-defective melanoma cells. Virus replication was required for their oncolytic activity. Cisplatin enhanced the oncolytic activity of delNS1 viruses. The cytotoxic drug increased delNS1 replication and delNS1-induced caspase-dependent apoptosis. Interference with MEK/ERK signalling by RNAi-mediated depletion or the MEK inhibitor U0126 did not affect the oncolytic effects of the delNS1 viruses. In oncolysis sensitive melanoma cells, delNS1-IL-15 (but not delNS1) infection resulted in the production of IL-15 levels ranging from 70 to 1140 pg/mL in the cell culture supernatants. The supernatants of delNS1-IL-15-infected (but not of delNS1-infected) melanoma cells induced primary human natural killer cell-mediated lysis of non-infected tumour cells. In conclusion, we constructed a novel oncolytic influenza virus that combines the oncolytic activity of delNS1 viruses with immunostimulatory properties through production of functional IL-15. Moreover, we showed that the oncolytic activity of delNS1 viruses can be enhanced in combination with cytotoxic anti-cancer drugs.